2004
DOI: 10.1104/pp.104.040832
|View full text |Cite
|
Sign up to set email alerts
|

Floral Meristem Identity Genes Are Expressed during Tendril Development in Grapevine

Abstract: To study the early steps of flower initiation and development in grapevine (Vitis vinifera), we have isolated two MADS-box genes, VFUL-L and VAP1, the putative FUL-like and AP1 grapevine orthologs, and analyzed their expression patterns during vegetative and reproductive development. Both genes are expressed in lateral meristems that, in grapevine, can give rise to either inflorescences or tendrils. They are also coexpressed in inflorescence and flower meristems. During flower development, VFUL-L transcripts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
0
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 68 publications
(70 reference statements)
8
90
0
11
Order By: Relevance
“…Interestingly, the expression analyses performed for the entire MIKC family showed that only the two previously analyzed genes VvFUL-L and VvAP1 were highly expressed in tendrils, while VvFUL was highly expressed in latent buds and during flower meristem initiation and flower development. The early and high expression of VvFUL in latent buds during flowering transition suggests a role in this process, as has been proposed for VvAP1 and VvFUL-L based on in situ hybridization experiments (Calonje et al, 2004). This is consistent with the role proposed for AP1 and FUL in the specification of inflorescence and flower meristem identity in Arabidopsis (Mandel and Yanofsky, 1995;Ferrándiz et al, 2000a).…”
Section: Mikc Genes and Tendril Developmentsupporting
confidence: 76%
See 3 more Smart Citations
“…Interestingly, the expression analyses performed for the entire MIKC family showed that only the two previously analyzed genes VvFUL-L and VvAP1 were highly expressed in tendrils, while VvFUL was highly expressed in latent buds and during flower meristem initiation and flower development. The early and high expression of VvFUL in latent buds during flowering transition suggests a role in this process, as has been proposed for VvAP1 and VvFUL-L based on in situ hybridization experiments (Calonje et al, 2004). This is consistent with the role proposed for AP1 and FUL in the specification of inflorescence and flower meristem identity in Arabidopsis (Mandel and Yanofsky, 1995;Ferrándiz et al, 2000a).…”
Section: Mikc Genes and Tendril Developmentsupporting
confidence: 76%
“…The second expression cluster included three major expression groups. The first group (VvAP1, VvFUL-L, and VvFUL) corresponded to genes expressed in tendrils and during flower meristem initiation and flower development, in agreement with their previously described expression patterns (Calonje et al, 2004). The second group corresponded to genes expressed during the differentiation of the outer flower whorls, including VvFLC1 and VvFLC2.…”
Section: Expression Analyses Of Mikc Genessupporting
confidence: 58%
See 2 more Smart Citations
“…Several flowering-related genes, including LFY, TFL1, and AP1 homologs, have been isolated from grapevine (Vitis vinifera L.), citrus (Citrus sinensis Osbeck), kiwifruit (Actinidia deliciosa C. F. Liang & A. R. Ferguson), and apple (Malus domestica Borkh.) (Boss et al, 2001(Boss et al, , 2006Calonje et al, 2004;Carmona et al, 2002;Jeong et al, 1999;Joly et al, 2004;Kotoda et al, 2000Kotoda et al, , 2002Kotoda and Wada, 2005;Pillitteri et al, 2004;Sung et al, 1999Sung et al, , 2000Wada et al, 2002;Walton et al, 2001). We previously isolated and compared LFY and TFL1 homologs from six maloid fruit trees, including Japanese pear and quince, to elucidate the molecular basis of the differences in inflorescence architecture (Esumi et al, 2005); however, the derived amino acid sequences differed only slightly in their primary structures.…”
Section: Introductionmentioning
confidence: 99%